Sistem Informasi Geografis Pemetaan Pasar Tradisional Daerah Kota Cilacap Berbasis Website - Indah Nuryohandi; Agus Susanto; Antonius Agung Hartono (Politeknik Negeri Cilacap, 2021)
The people's market is a meeting place for sellers and buyers, which is indicated by direct transactions between sellers and buyers, either through kiosks, booths and open bases. Geographically, the information available at the Trade Office, Cooperatives, Small and Medium Enterprises (DPKUKM) and Market regarding the situation and location of the market is not clear, there is no media used by the market to convey information and manage the market. The market head delivers information verbally to the agency. System development uses the waterfall method, blackbox method, actor feature functionality testing, and scenario testing. This research aims to make a website-based geographic information system can help facilitate the head of the market and offices in conveying market-related news information, as a promotional medium for each market in promoting it to visitors. The results of this system research can display market location information in the form of maps, existing facilities in the market and pelapak maps.